Hacking Techniques in Data Theft: A Literature Study on Ethical Problems in Information Technology - Rahman Rulli Arjiansa (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2024)
The advancement of information technology (IT), particularly in computing and internet-based communication, has significantly influenced modern human life. However, rapid digital development has also increased vulnerabilities, especially in data security. One of the most prominent ethical issues in today’s IT landscape is data theft, encompassing a wide range of cybercrimes such as hacking, spyware, and phishing. These attacks employ sophisticated techniques including pharming, spoofing, and identity fraud that lead to serious consequences such as financial loss, privacy invasion, reputational damage, and compromised national security. This study explores the phenomenon of data theft, identifies various hacking techniques used to obtain information illegally, and discusses the ethical dimensions of IT practices. Using a literature-based descriptive qualitative approach, this study reviews prior research to synthesize preventive ethical strategies in information management. The findings reveal that enhancing ethical awareness, strengthening data protection measures, and fostering collaboration among IT stakeholders are crucial to mitigating data-theft risks and maintaining integrity in digital ecosystems.